2009
DOI: 10.1016/j.bbi.2008.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Attachment avoidance predicts inflammatory responses to marital conflict

Abstract: Marital stress has been associated with immune dysregulation, including increased production of interleukin-6 (IL-6). Attachment style, one's expectations about the availability and responsiveness of others in intimate relationships, appears to influence physiological stress reactivity and thus could influence inflammatory responses to marital conflict. Thirty-five couples were invited for two 24-hour admissions to a hospital research unit. The first visit included a structured social support interaction, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 48 publications
7
84
2
4
Order By: Relevance
“…In one study, avoidantly attached husbands and wives showed heightened inflammatory (IL-6) responses to a marital conflict discussion [50]. In another study, more avoidantly attached women recovered more slowly from induced skin wounds over the course of discussions with their dating partner.…”
Section: Immune Responsesmentioning
confidence: 99%
“…In one study, avoidantly attached husbands and wives showed heightened inflammatory (IL-6) responses to a marital conflict discussion [50]. In another study, more avoidantly attached women recovered more slowly from induced skin wounds over the course of discussions with their dating partner.…”
Section: Immune Responsesmentioning
confidence: 99%
“…Most people experience conflicts in their communications as infinitely intensive (Halford, 2001;HoltLunstad, & Birmingham, 2008). Conflicts are also positively correlated with inappropriate psychological well-being conditions (Galinsky and Waite, 2014;Hawkins, & Booth, 2005), insecure attachment style (Gouin, 2009), several psychiatric disorders such as internalizing disorders (Brock, & Lawrence, 2011), depression (Wang , Wang , & Miller 2014), anxiety disorders (Doss, Simpson, & Christensen, 2004), sexual dysfunction disorders (Metz, & Epstein, 2002), and physical health problems (Galinsky and Waite, 2014) such as hypertension (Holt-Lunstad, & Birmingham, 2008), chronic pain (Cano et al, 2004) and ischemic heart diseases (Galinsky and Waite, 2014). The more unsatisfied the spouses are with their marital status, the higher is the probability of divorce (Gottman, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…For instance, secure individuals provide responsive support and are better at managing negativity in their close relationships (Kane et al, 2007). Although there is a literature linking attachment styles to health outcomes (e.g., Gouin et al, 2009), work would also be needed that directly models support and conflict as mediators of any such links (Pietromonaco et al, 2012). Relationship goals have also been linked to support and conflict, although none of this work to date appears to have been applied to the health domain (Canevello & Crocker, 2011;Gable, 2006).…”
Section: On Building Stronger Bridges Between Relationship Science Anmentioning
confidence: 99%